REINFORCEMENT THE INDEPENDENT OF CULTURAL VILLAGE COMMUNITIES BY E-TOURISM IN KOTO SENTAJO - Firzal, Yohannes; Yesicha, Chelsy; Sulistyani, Andry; ., Safri; Sari, Genny Gustina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This article is a research conducted in the cultural tourism village of Koto Sentajo. The research was initiated by creating a network with various related advice and assistance in improving the quality of local community skills through training and hands-on practice which aims to be able to help increase income for the village. Apart from the collection of Rumah Godang, this tourist village is also enriched with natural beauty such as protected forests, rice fields and rivers that have interesting potentials for the benefit of local residents. However, all the potential of this tourist village has not been well mapped as a tourist attraction and is supported by tourism promotion management. This then becomes an interesting object of research on how all the potentials of this tourist village can be mapped and helps strengthen community independence in managing existing tourism potential. This research puts forward the method of direct local community participation in data collection which is also supported by the method of interviews, observation and literature study. The research succeeded in carrying out a comprehensive mapping of tourism potential on a number of tourist objects, cultural attractions, culinary delights and local arts. In terms of strengthening the role, the community has begun to be able to receive live in tours through various involvement of tourism activities in their daily activities. This new phenomenon in the life of cultural village communities is an indication that the community can grow and develop in terms of tourism through inclusive behavior in accepting tourists and at the same time promoting local tourism potential towards e-tourism